Los cuentos infantiles en el lenguaje oral en niños y niñas de 4 a 5 años de edad del centro de educación inicial “Teresa León de Noboa, provincia de Bolívar, cantón Guaranda, período 2024. - Reyes Ibarra, Odalys Thalia. (2025)
This research project focuses on analyzing the impact that children's stories have specifically on the oral language development of boys and girls between 4 and 5 years of age at the “Teresa León de Noboa” Early Education Center, province of Bolívar, Canton. Guaranda period 2024. It is carried out through a qualitative methodology, which allows us to explore in depth the characteristics, experiences and advances of children's oral language through direct observation. The theoretical framework of this research project is based on theories and approaches related to the development of oral language in early childhood and the pedagogical use of children's stories as an educational tool. Likewise, the impact of children's stories on the stimulation of oral language is analyzed, highlighting their ability to expand vocabulary, improve sentence structuring and promote creativity. Likewise, in this project it is evident that children's stories do positively influence the development of oral language since through the use of different activities implemented to tell stories, children achieve better development. This is because through storytelling the acquisition of language and improvement in the structuring of short sentences is better promoted